2012
DOI: 10.1039/c2np00084a
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Aspergillus secondary metabolite research in the post-genomic era

Abstract: This review studies the impact of whole genome sequencing on Aspergillus secondary metabolite research. There has been a proliferation of many new, intriguing discoveries since sequencing data became widely available. What is more, the genomes disclosed the surprising finding that there are many more secondary metabolite biosynthetic pathways than laboratory research had suggested. Activating these pathways has been met with some success, but many more dormant genes remain to be awakened.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
194
1
8

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 244 publications
(204 citation statements)
references
References 144 publications
(175 reference statements)
1
194
1
8
Order By: Relevance
“…VIII). The fact that two 10 R -HPODE-producing subfamilies have evolved in parallel strengthens previous reports that 10 R -HPODE is of biological importance ( 44 ).…”
Section: Discussionsupporting
confidence: 70%
“…VIII). The fact that two 10 R -HPODE-producing subfamilies have evolved in parallel strengthens previous reports that 10 R -HPODE is of biological importance ( 44 ).…”
Section: Discussionsupporting
confidence: 70%
“…19) However, it was reported that certain strains of A. niger could produce ochratoxin and fumonisin while some strains of A. oryzae could produce aflatoxin and cyclopiazonic acid. 20) In the present study, these mycotoxins were not detected in the fermented KGB (data not shown).…”
Section: Methodsmentioning
confidence: 69%
“…Racemic 9-and 13-HPODE were obtained by photo Fungal pathogens may secrete LOXs during invasive growth to generate reactive oxygen species and lysis of membranes. Fungal LOXs may also regulate biosynthesis of secondary metabolites and toxins, including biosynthesis of jasmonates ( 11,(13)(14)(15)(16)(17).…”
Section: Methodsmentioning
confidence: 99%